Knowledge and Associated Factors Influencing Insecticide-Treated Net Usage among Pregnant Women in Selected Health Facilities in Ekiti State - Sunmola, K. A. (African Journal of Stability and Development (AJSD), 2025)
Malaria is one of the leading causes of maternal mortality in sub-Saharan Africa, Nigeria inclusive. This study assessed knowledge of Insecticide-Treated Net (ITN) as well as socio-demographic factors associated with ITN utilisation among 1,285 pregnant women of childbearing age, who attended antenatal care, pooled from selected health facilities across the 16 Local Government Areas of Ekiti. Data were analysed descriptively using frequency counts and percentages, while the Chi-square test and binary logistic regression were employed at the bivariate and multivariate stages, respectively. Findings revealed that awareness and overall usage of ITNs were high. Education was a strong and very significant predictor of ITN use (p < 0.05 for all groups). Specifically, respondents who had primary school education were 81% less likely to use ITNs (OR = 0.19, 95% CI: 0.78–0.45), secondary education were less likely (OR = 0.99, 95% CI: 0.45–0.22), and tertiary education were even less likely (OR = 0.11, 95% CI: 0.50–0.25). The study concludes that Universal ITN coverage and utilisation will not be achieved through distribution campaigns alone but through focused, context-specific interventions that interact with the psychological, cultural, and economic forces controlling women’s health behaviour.